Investigating travel motivations for visiting urban destinations in the Republic of Serbia - Podovac, Milena (Turyzm/Tourism, 2022)
The aim of this article is to examine travel motivations for visiting urban destinations in the Republic of Serbia. Differences among the travel motives according to tourists’ demographic characteristics were also analyzed. The research was conducted from June 2018 to July 2019 on tourists who visited urban destinations in Serbia (Belgrade, Novi Sad, Niš and Kragujevac). The analysis included 390 valid answers from respondents. The research results, which are presented in the article, have shown that tourists visit urban destinations in Serbia for business, education, family and sightseeing. The contribution of this study is reflected in the identification of key travel motives for visiting urban destinations in Serbia and this can help those preparing a tourist offer to adjust their services to the needs and requirements of such tourists.